2020
DOI: 10.3390/su12187295
|View full text |Cite
|
Sign up to set email alerts
|

A Cultural Heritage Framework for Preserving Qatari Vernacular Domestic Architecture

Abstract: Architecture and urbanism in the Arabian Gulf region, and specifically in the State of Qatar, offer many scenes to observe the loss of urban identity and cultural heritage in the various components of the built environment, including residential architecture. Many people attribute this to rapid development in globalization and the adoption of Western standardization in planning and design practice. Conversely, in the field of architectural sociology, scholars argue that socio-cultural factors such as privacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Socio-cultural concepts are comprehensive and are indirectly related to settlement design (Mentayani & Muthia, 2017). Place in different concepts raises the complexity of the term in its comprehensive implementation regarding the relationship between social and spatial (Al-Mohannadi et al, 2020;Kamalipour & Zaroudi, 2014). Several studies set an interdisciplinary approach when constructing the form and context of the discipline of this paper, ranging from the spatial form of the house and culture, and the settlement process is a cultural phenomenon, the physical form and spatial configuration of the house are influenced by the cultural context (Rapoport, 1969).…”
Section: Social Culture and Settlement Formmentioning
confidence: 99%
“…Socio-cultural concepts are comprehensive and are indirectly related to settlement design (Mentayani & Muthia, 2017). Place in different concepts raises the complexity of the term in its comprehensive implementation regarding the relationship between social and spatial (Al-Mohannadi et al, 2020;Kamalipour & Zaroudi, 2014). Several studies set an interdisciplinary approach when constructing the form and context of the discipline of this paper, ranging from the spatial form of the house and culture, and the settlement process is a cultural phenomenon, the physical form and spatial configuration of the house are influenced by the cultural context (Rapoport, 1969).…”
Section: Social Culture and Settlement Formmentioning
confidence: 99%
“…Kong et al demonstrated the appearance of a stepwise spatial hierarchy of space and verified that spatial intelligibility is high by analyzing European perimeter block housing [18]. Many studies also compare the interaction behavior and social culture associated with a space by understanding that the courtyard residential environment in any country is where interaction occurs [19][20][21].…”
Section: Literature Review 21 the Residential Environment Of The High-rise Apartments And Perimeter Block Housingmentioning
confidence: 99%
“…Studies on the spatial form of Qatari vernacular houses-Siheyuan-reflect the essence of social form in the ancient Qatari settlements. Socio-cultural patterns, namely privacy, gender segregation and hospitality, determine the spatial form of Qatari vernacular houses [12,13]. Traditional Iranian architecture organizes space according to people's beliefs, one of which is respect for private life and self-esteem [14].…”
Section: Introductionmentioning
confidence: 99%